Poor Readability of AOSSM Patient Education Resources and Opportunities for Improvement. Issue 11 (30th October 2018) - Kakazu, Rafael; Schumaier, Adam; Minoughan, Chelsea; Grawe, Brian
Background: Appropriate education on the disease processes associated with orthopaedic pathology can affect patient expectations and functional outcome. Hypothesis: Patient education resources from the American Orthopaedic Society for Sports Medicine (AOSSM) are too complex for comprehension by the average orthopaedic patient. Study Design: Cross-sectional study. Methods: Patient education resources provided by the AOSSM were analyzed with software that provided 10 readability scores as well as opportunities for improving readability. The readability scores were compared with the recommended eighth-grade reading level. Results: A total of 39 patient education resources were identified and evaluated. The mean ± SD reading grade-level scores were as follows: Coleman-Liau Index, 12.5 ± 1.11; New Dale-Chall Readability Formula, 10.9 ± 1.37; Flesch-Kincaid Grade Level, 9.9 ± 1.06; FORCAST Readability Formula, 11.4 ± 0.51; Fry Readability Formula, 12.8 ± 2.79; Gunning Fog Index, 11.9 ± 1.37; Raygor Readability Index, 13.1 ± 2.37; Simple Measure of Gobbledygook, 12.3 ± 0.90; Automated Readability Index, 11.2 ± 1.18; and New Automated Readability Index, 10.6 ± 1.27. After averaging the reading grade-level scores, only 1 patient education resource was found to be written at an 8th- to 9th-grade level, and 14 (36%) were written above a 12th-grade level. All scores were significantly different from the eighth-grade level ( P < .0065). The percentage of complex words and long words were 19.6% ± 2.67% and 41.4% ± 3.18%, respectively. Conclusion: Patient education resources provided by the AOSSM are at a significantly higher reading level than recommended. Simple changes can drastically improve these scores to increase health literacy and possibly outcome.